Phantom development for radiographic image optimization of chest, skull and pelvis examination for nonstandard patient - Miranda, Diana Rodrigues de Pina [UNESP]; Duarte, S. B.; Netto, T. Ghilardi; Morceli, J. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2009)
The construction of the adapted patient equivalent phantom (APEP) to simulate the X-ray scattering and absorption by chest, skull and pelvis of nonstandard patient in conventional radiographic equipment is presented. This APEP system is associated to the pre-existing realistic-analytic phantom (RAP) [Pina, D.R., Duarte, S.B., Ghilardi Netto, T., Trad, C. S., Brochi, M.A.C., Oliveira, S.C. de, 2004. Optimization of standard patient radiographic images for chest, skull and pelvis exams in conventional X-ray equipment. Phys. Med. Biol. 49, N215-N226] forming the coupled phantom (RAP-APEP), which is used to establish an optimization process of radiographic images of chest, skull and pelvis for nonstandard patients. A chart of the optimized radiographic technique is established covering a wide range of nonstandard patient thickness, and offering a dose reduction in comparison with those techniques currently used. Different validation processes were applied to confirm the improving of the radiographic image quality when techniques of the established chart are used. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Radiographic technique; Quality image; Phantom; Nonstandard patient; Reduction dose